Representation of voices and social actors in Al-Jazeera and CNN news coverage of the 2014 Israeli-Gaza conflict / Abdallah Z.A. Warshagha - Abdallah Z.A. , Warshagha (2019)
The 2014 Israeli-Gaza conflict is regarded as one of the violent and unforgettable conflicts in modern history (Qawariq, 2016). The language used in the news websites was seemingly disparate in terms of representing the Palestinians in Gaza and the Israelis. This study seeks to examine how Al-Jazeera and CNN represented the Israelis and the Palestinians in the news during that conflict. This research explores the methods of intertextuality in representing the underlying relations of power and ideology in the contexts of news articles in the Aljazeera and CNN’s websites. The sample of the study consists of 40 headlines and 18 news articles taken from both news websites, and adopts Fairclough’s (1995) three-dimensional approach, Kristiva (1986) and Van Leeuwen’s (1996) socio-semantic representation within discourse analysis in order to examine the function of intertextuality. The study examines how the voices and social actors are represented through employing certain strategies and linguistic representations to meet certain ideological and power stanzas. It can be observed that there is a strong relationship between power, ideology and language in the Aljazeera and CNN's news website articles. The study finds that the most common forms of intertextuality used by the CNN and AJE’s news writers are indirect/direct reported speeches and/or inclusive/exclusive voices. Such forms can allow the news writers to represent the voices and the social actors with using certain linguistic representations e.g. direct/indirect reported speeches and activated/passivated voice. The study shows how the devices of intertextuality can play a dynamic role in representing the news discourse with certain linguistic representations that suit specific ideas and ideological objectives.